Estimation of Serum Magnesium Levels in the Patients of Acute Cases of Bronchial Asthma - Fozia Shaikh, Syeda Nargis Fatima, Muhammad Amir Alsabah, Zeeshan Ul Haq, Mubeena Laghari, Ali Raza Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The prevalence of Bronchial Asthma increasing day by day at Asian countries due to environmental& nutritional factors. Magnesium plays important role in the prevention of bronchial asthma because magnesium causes the relaxation of smooth muscles & dilatation of bronchioles. This study was aimed to estimate the serum magnesium level in the patients of newly diagnosed cases of acute asthma. Methodology: This cross sectional study was conducted by the Department of Biochemistry with collaboration Pulmonology OPD LUMHS Hospital Hyderabad. Total 55 newly diagnosed cases of acute asthma between the age of 31 -6 0years were selected with their own consent for this study. The patients were selected on the basis of GINA guidelines. Serum magnesium level was estimated by kit method by auto analyzer. Results:total 55 newly diagnosed cases of acute asthma divided in to three groups according to age Gr:-I (31 -40 years) Gr:-II (41-50 years) Gr:-III (50-60 years). Serum mean serum magnesium levels in Gr:-I was 1.21 ± 0.12 mg/dl, Gr:-II 1.01 ± 0.09 mg/dl while in Gr:-III 0.97 ± 0.87 mg/dl. The mean serum magnesium level significantly decline in group –II & III. Conclusion:Our study concluded that serum magnesium level has decline in the cases of acute attacks of bronchial asthma and also noted in this study that serum magnesium decline directly proportional with elder age.